Análise sistemática de indicadores econômicos e setoriais para planejamento estratégico no setor da construção civil - Machado, Marcos William Kaspchak (2016)
The aim of this study was to propose a systematic analysis of the variables that influence the process of strategic decision making in the construction sector organizations. Through the theoretical framework, raised through a systematic review, were identified the eight variables, employment and income, investments, domestic production, inflation, finance and housing credit, production of inputs, prospects of managers and company number, that influence the decision-making process of the construction sector organizations. These variables based the collection of time series of economic and sectorial indicators representing the behaviour of each sector variables. The time series, samples of ten years (2006 to 2015) were analysed statistically by estimating the dispersion and correlation curve. For the correlation analysis, the indicators were correlated in two dimensions, between the indicators of the same variable, called the one-dimensional, and with indicators of other variables, two-dimensional. In accordance with the systematic proposal, through the theoretical framework and the correlation coefficients found, it was possible to develop guidelines for the strategic positioning of organizations in the construction sector in accordance with the area of decision-making and with the strategic criteria adopted by companies. The result of the correlations showed that all variables are indicators with significant relationships. Employment and income variables, financing and credit investments presented results that show the importance of the sector in the implementation of government resources and social development. In addition, production indicators, inflation and prospects of managers demonstrated by two-dimensional correlation analysis, that the reduction in domestic production and high inflation affect the perspective of managers of the construction industries, however, according to analysis dispersion, the short-term the strategic decisions do not change. Thus, the system of indicators demonstrated that the use of external analysis process in strategic decision making and reduces the risk becomes more competitive organizations.